2021
DOI: 10.1038/s41597-021-01006-6
|View full text |Cite
|
Sign up to set email alerts
|

AusTraits, a curated plant trait database for the Australian flora

Abstract: We introduce the AusTraits database - a compilation of values of plant traits for taxa in the Australian flora (hereafter AusTraits). AusTraits synthesises data on 448 traits across 28,640 taxa from field campaigns, published literature, taxonomic monographs, and individual taxon descriptions. Traits vary in scope from physiological measures of performance (e.g. photosynthetic gas exchange, water-use efficiency) to morphological attributes (e.g. leaf area, seed mass, plant height) which link to aspects of ecol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 298 publications
3
44
0
Order By: Relevance
“…We also compared the difference in flowering period lengths between woody and herbaceous species using Welch's T-tests, with one t-test for all species pooled (n = 2790) and multiple t-tests with Bonferroni correction (alpha = 0.05/6 = 0.008) for species by biome (n = 87-1160). Data on woodiness were sourced from AusTraits (Falster et al, 2021). We also confirmed that species range size was positively correlated with flowering period length using OLS regressions for all available species (n = 2819) as an indication of the potential intraspecific variation in flowering phenology captured by specieslevel data.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We also compared the difference in flowering period lengths between woody and herbaceous species using Welch's T-tests, with one t-test for all species pooled (n = 2790) and multiple t-tests with Bonferroni correction (alpha = 0.05/6 = 0.008) for species by biome (n = 87-1160). Data on woodiness were sourced from AusTraits (Falster et al, 2021). We also confirmed that species range size was positively correlated with flowering period length using OLS regressions for all available species (n = 2819) as an indication of the potential intraspecific variation in flowering phenology captured by specieslevel data.…”
Section: Discussionsupporting
confidence: 59%
“…All observations were aggregated to the species level, removing any subspecies or variants, after taxonomic alignment to the Australian Plant Census (Council of Heads of Australasian Herbaria, 2021) following methods in (Falster et al, 2021)).…”
Section: Community Floristic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Along with existing plant-trait databases (e.g. [160,161]), other ecological datasets can be immediately applied to CHES models such as an invasive plant dataset with associated bioclimatic variables [162], a database of ecosystem services [163] as well as land use datasets that already contain human environment coupling that can further motivate future models [164][165][166].…”
Section: (B) Incorporating New Datamentioning
confidence: 99%
“…We encourage the integration of trait data generated from SSE studies (and others) into large, global trait databases such as eFLOWER (Sauquet et al, 2017), TRY (Kattge et al, 2020) or more focused databases (e.g. AusTraits (Falster et al, 2021)). These will act as important resources as researchers consider several traits in tandem when testing for context-dependent effects of traits, or when disentangling the traits hiding in the hidden-state approaches.…”
Section: Knowledge Gaps and Future Avenuesmentioning
confidence: 99%